PEMBUATAN MODUL KIT KONVERSI KENDARAAN LISTRIK SEBAGAI SARANA PEMBELAJARAN VOKASI - Mufti Reza Aulia Putra; Muhammad Nizam; Feri Adriyanto; Inayati; Warindi; Joko Slamet Saputro; Miftahul Anwar; Agus Ramelan; Hari Magfiroh; Chico Hermanu Brilianto Apribowo (CV. Kalimasada Group, 2025)
This study aims to develop an electric vehicle conversion kit module as a vocational learning tool at SMK Muhammadiyah 1 Surakarta. The research method used is Research and Development (R&D), which includes the design, production, and trial phases of the module. Evaluation was conducted through concept comprehension tests and practical skill assessments before and after using the module. The results indicate that the electric vehicle conversion kit module significantly enhances students' understanding and skills related to Electric Motorized Vehicles (KBL) technology. Furthermore, the study's findings were published in a national ISSN journal and mass media. As an additional output, a copyright for the module was obtained, demonstrating its innovative contribution to vocational education and electric vehicle technology.